17 Establishing a physiologically relevant in vitro model for ischaemic stroke injury in brain endothelial cells. (December 2018) - Warpsinski, Gabriela; Srivastava, Salil; P Keeley, Thomas; Fraser, Paul; E Mann, Giovanni
Abstract : Introduction: Ischaemic stroke is a major contributor to adult disability in developed countries. However, the only clinically approved acute treatment is delivery of the thrombolytic agent, alteplase, that has a narrow window of 6 hour post-stroke. To better screen treatments for ischaemic stroke, a more relevant in vitro model for ischaemic stroke is needed. Numerous studies have demonstrated that brain microvascular endothelial cells experience an O2 environment ranging from 4–7 kPa, on the contrary most cell culture studies are conducted under ambient O2 levels, 18 kPa that inevitably expose cells to hyperoxia. To better understand the consequences of O2 levels, mouse brain endothelial cell line, bEnd.3, was cultured long-term under 18 kPa or 5 kPa O2 levels, and cell sensitivity to in vitro model of ischaemic stroke was assessed. Methods: bEnd.3 cells were cultured long term (5 days) under 18 kPa or 5 kPa O2 levels and subjected to oxygen-glucose deprivation (OGD) for 2–12 hour. Cell viability was then assessed using ethidium bromide staining. Intracellular O2 content was also measured using an O2 sensitive nanoparticle probe, MitoXpress-Intra (2.5 µg/ml), in an O2-regulated plate reader from BMG Labtech. Statistical analysis was performed using student's t-test or two-way analysis of variance (ANOVA) followed by Bonferroni Post Hoc test. Results: In the present study, the bEnd.3 cell phenotype was determined following long-term (5 days) culture under 18 kPa or 5 kPa O2. Under 5 kPa O2, the intracellular O2 content of bEnd.3 cells was approximately 3.6 kPa O2 (n=3) and this finding is in agreement with other studies that have reported in vivo O2 content of the microvasculature. bEnd.3 cells cultured under 5 kPa also exhibited lower intracellular glutathione content compared to cells cultured under 18 kPa O2 (20.6 vs 29.9 mmol/mg protein, n=4, p=0.003). Furthermore, bEnd.3 cells cultured under 5 kPa O2 exhibited greater sensitivity to OGD-induced cell death, with increased ratio of dead to live cells seen under 2 hour OGD (0.42 vs 0.05, n=3, p=0.0002). Conclusions: The majority of cell culture studies have conducted experiments under hyperoxia. The present study highlights the importance of conducting cell culture studies under physiological O2 levels, as demonstrated by the different phenotype resulted from long-term culture under physiological O2 levels. This work was supported by Grant (FS/13/66/30445) from the British Heart Foundation. The authors declare no conflicts of interest.